Personal Peacefulness and Cyber-Bystanding of Internet Users in Indonesia - Nurfitriany Fakhri; Faradillah Firdaus; Irdianti; Sahril Buchori; Ria Andriany Fakhri (Jurnal Pendidikan Agama Islam)
Purpose – As internet use grows, cyberbullying has become more common, especially in schools. People who witness cyberbullying (cyber-bystanders) strongly influence these incidents, but little is known about their behavior. To reduce cyberbullying, we need to understand what affects cyber-bystanding. This study examines whether personal peacefulness can predict how people act as cyber-bystanders.